Municipal transfers system as regional policy instruments in the Nordic countries - Jan Mønnesland (European Regional Science Association (ERSA), 2002)
While regional incentive programmes attract high attention in the regional policy debate, less attention is devoted towards municipal transfer systems. Nevertheless, these systems will in many countries redistribute more financial resources between regions than the more narrowly defined regional policy programmes. The municipal transfer systems are described briefly for the 5 Nordic countries. The systems are normally based on two pillars, one intending to equalise differences in local income potentials, and one to compensate for differences in the needs for public services. Especially for the last mentioned pillar, it differs between the countries to what extent credit is given to regional policy elements (i.e. periperiality, weak industrial and employment structure, weak demographic perspectives etc.). Also the level of equalisation ambitions differ between the countries. As a genereral tendency, high ambitions tend to gain those areas being targeted in the regional policy, while low ambitions tend to gain the more central areas. The paper ends up in a description on the regional distribution effect of the programmes. The mix between implicit and explicit regional policy elements is discussed on a comparative perspective.
Keywords: 330